The effect of octapressin on renal and intrarenal blood flow in cirrhosis of the liver. Issue 4 (April 1972) - Kew, M. C.; Varma, R. R.; Sampson, D. J.; Sherlock, Sheila
Abstract : The effect of octapressin (2-phenylalanine-8-lysine vasopressin) on renal and intrarenal blood flow was studied in 11 normotensive cirrhotic patients with abnormal renal perfusion. Renal haemodynamic changes were assessed with the 133 Xenon washout technique. Of the six patients given suppressor doses of octapressin intravenously renal blood flow improved in one only. A further three patients responded to the drug in a dose which increased the mean arterial pressure by 5 or more mm Hg. The increase in mean renal blood flow was accompanied by an improvement in renal cortical perfusion. In two patients renal blood flow decreased after the administration of octapressin. These findings, in conjunction with previous reports, suggest that octapressin will only consistently improve renal perfusion in cirrhotic subjects who are hypotensive and in whom the mean arterial blood pressure is raised by the drug, but do not exclude the possibility that octapressin may have a direct renal circulatory effect in some patients.